2005
DOI: 10.1302/0301-620x.87b3.14788
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-supplemented impacted bone allografts in infected hip arthroplasty

Abstract: Bone allografts can store and release high levels of vancomycin. We present our results of a two-stage treatment for infected hip arthroplasty with acetabular and femoral impaction grafting using vancomycin-loaded allografts. We treated 29 patients (30 hips) by removal of the implants, meticulous debridement, parenteral antibiotic therapy and second-stage reconstruction using vancomycin-supplemented impacted bone allografts and a standard, cemented Charnley femoral component. The mean follow-up was 32.4 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(73 citation statements)
references
References 54 publications
0
70
0
3
Order By: Relevance
“…The theoretical disadvantage is the risk of colonisation of avascular grafts. Early reports of allograft use have shown excellent results [5].…”
Section: Second Stage Reconstruction Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical disadvantage is the risk of colonisation of avascular grafts. Early reports of allograft use have shown excellent results [5].…”
Section: Second Stage Reconstruction Optionsmentioning
confidence: 99%
“…Buttaro et al [5] reported 30 cases who received vancomycin-supplemented impaction bone grafting. Antibiotics were not added to cement used in the revision prosthetics.…”
Section: Second Stage Reconstruction Optionsmentioning
confidence: 99%
“…Other porous biodegradable materials for local antibiotic delivery, like collagen sponges [46], cancellous bone [47], [48,49] and bioceramics [50], were not specifically designed to protect implanted biomaterials and their use for infection prevention in trauma is currently limited. Biodegradable polymers and sol-gel coatings have also been investigated to provide a controlled antibiotic release on titanium [51,52] or hydroxyapatite implants [53].…”
Section: Discussionmentioning
confidence: 99%
“…The impaction grafting technique has been reported with good results in revision hip surgery: this technique restores bone stock, and morcellised bone grafts can be used as carriers of antibiotics in cases of previous infections [3,4,7,8,20,23]. When segmental defects are present, the combination of morcellised grafts with metal meshes has been associated with a favourable outcome [8,12,22].…”
Section: Discussionmentioning
confidence: 99%